Kinetic aspects of a dried thin layer carrot in a heat pump dryer - Juan Carlos Gómez-Daza (Dyna, 2016)
This article presents a mathematical model for drying thin layer carrot slices (Daucus carota) using a heat pump dryer (HPD). To select the equation that best describes the drying curve, 10 semi-theoretical and/or empirical models were evaluated. The parameters were determined using the Sigma-Plot® program, and their goodness of fit was compared using the correlation coefficient, R2; Chi-squared, c2; standard error of the estimate (SEE) and root mean square error (RMSE). Additionally, the effect of the relative moisture, sample thickness and air velocity on the effective diffusivity of the process was evaluated using a response surface tool. Although all the models correctly fit the experimental data, based on the statistical tests, the Wang-Singh model was selected as the best.